The Effects of Psychological Factors, Career Level, and External Clinical Workload on Physician Performance: A Cross-Sectional Study of Dual-Practice Physicians at Mitra Plumbon Hospital, Indonesia - Tiara Kusumawiyanti; Muhardi; Dede R. Oktini (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Physician performance is a critical determinant of hospital service quality because it directly influences the effectiveness, professionalism, and quality of patient care. Both individual and work-related factors contribute to physician performance, including psychological factors, career development, and workload arising from clinical practice outside the primary hospital. This study aimed to examine the effects of psychological factors, career level, and external clinical practice workload on physician performance among dual-practice physicians at Mitra Plumbon Hospital, Majalengka, Indonesia. A quantitative study employing descriptive and explanatory approaches was conducted using a structured questionnaire administered to physicians who met the study criteria. The collected data were analyzed using descriptive statistics and multiple linear regression to evaluate the relationships among the study variables. The results indicated that psychological factors, career level, external clinical practice workload, and physician performance were generally perceived to be at a very high level. Psychological factors, reflected in work motivation, personal satisfaction, organizational commitment, and self-efficacy, had a significant positive effect on physician performance. Career level, represented by opportunities for promotion, professional recognition, and competency development, also demonstrated a significant positive influence on physician performance. In contrast, external clinical practice workload had a significant negative effect on physician performance. Greater involvement in clinical practice outside the hospital increased the likelihood of fatigue, reduced concentration, and limited time available for hospital responsibilities, thereby adversely affecting physician performance. Overall, psychological factors and career level positively influenced physician performance, whereas external clinical practice workload negatively influenced physician performance. These findings suggest that strengthening physicians' psychological well-being, implementing transparent career development systems, and effectively managing external clinical practice workload are essential strategies for improving physician performance and enhancing the quality of hospital services.